Pinewood Anatomy of a Film Studio in Post-war Britain - Street, Sarah; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book examines how Pinewood came to be Britain$1 (Bs dominant film studio complex, focusing on key years following the Second World War. It presents a revisionist, micro history organized around key themes that are crucial to understanding the studios$1 (Blongevity during a particularly turbulent period. Pinewood$1 (Bs survival at a time when other major film studios such as Denham closed, is explained. The book examines contemporary insights into how Pinewood$1 (Bs technologies and practices compared to Hollywood$1 (Bs when filmmaking methods were being scrutinized. Thirteen films produced in 1946-7 are analysed in detail, tracking how economic pressures engendered many creative techniques and innovative technologies. Prevailing cultures of management and labour organization are foregrounded, as well as insights into being a studio employee. These are vividly brought to life through an in-depth focus on the in-house studio magazine the Pinewood Merry-Go Round which provides rare details of sports and leisure activities organized at the studios. Sarah Street is Professor of Film at the University of Bristol. Publications include British National Cinema (1997), Transatlantic Crossings: British Feature Films in the USA (2002), Colour Films in Britain: The Negotiation of Innovation, 1900-55 (2012), Chromatic Modernity: Color, Cinema, and Media of the 1920s (2019, with Joshua Yumibe), and The Eastmancolor Revolution (2021, with Keith M. Johnston, Paul Frith and Carolyn Rickards).s
1.Setting the film studio stage -- 2. Cultures of innovation at Pinewood.-3. In the studio and on location 1 -- 4. In the studio and on location 2 -- 5. Managerial culture and labour relations at Pinewood -- 6. Cultural life at Pinewood -- 7. Anatomy of Pinewood in transition -- Bibliography.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Motion pictures -- Great Britain; Motion pictures -- Production and direction; British Film and TV; Film and Television Production